UAV Laser scanning technology: a potential cost-effective tool for micro-topography detection over wooded areas for archaeological prospection. Issue 11 (1st November 2020) - Zhou, Wei; Chen, Fulong; Guo, Huadong; Hu, Mingyuan; Li, Qi; Tang, Panpan; Zheng, Wenwu; Liu, Jian'an; Luo, Rupeng; Yan, Kaikai; Li, Ru; Shi, Pilong; et al.
ABSTRACT: Airborne laser scanning (ALS) has recently been identified as a potential tool in topographic mapping for archaeological prospection. However, most existing applications in this field refers to manned ALS systems, for which the high operation and maintenance costs limits its application in small-scale archaeological investigation. In this paper, we conducted an exploratory study on the application of the unmanned aerial vehicle (UAV) laser scanning (ULS) system in ancient micro-topography detection over wooded areas. Compared with manned ALS technology, we analyzed the advantages and potentials of ULS technology for archaeological applications. Then we outlined existing mainstream survey-grade UAV-based laser scanners, data processing and visualization approaches. Furthermore, we performed case studies in three cultural heritage sites in Zhejiang Province, China using two representative mainstream survey-grade ULS systems. Results were then verified by an in-site investigation. Finally, the correct selection of ULS devices, the planning of data acquisition missions and the use of appropriate data processing methods specifically for archaeological prospection were discussed. This paper provides a cost-effective and flexible solution for micro-topography detection in wooded areas. ULS technology, as demonstrated here, can be an important supplement to existing archaeological investigation methods, particularly for small-scale areas, and has promising prospects in archaeological applications.